Strategi Pemberdayaan Ekonomi melalui Festival Budaya Olahraga Tradisional di Kalimantan Tengah - Harvianto, Yudo; Pujiati, Amin; Louk, Michael Johannes Hadiwijaya; Sinurat, Ridwan; Anam, Khaerul; Syaffruddin, Muhammad (Universitas Hamzanwadi, 2025)
This study aims to analyze the strategy of community economic empowerment through the Traditional Sports Culture Festival in Central Kalimantan. The method employed in this study is a literature review, by examining various scientific articles, official reports, and academic publications related to cultural festivals, traditional sports, and the creative economy published between 2000 and 2024. The results of the study showed that this festival succeeded in increasing the income of micro business actors (culinary and local crafts) during the event, as well as creating job opportunities for parking and transportation officers. The main strategies that support this success include: (1) integration of local culture in economic activities, (2) collaboration between stakeholders (government, indigenous communities, business actors), and (3) digital-based promotion to attract visitors. This study concludes that traditional sports culture festivals can be an effective instrument for empowering the local economy if supported by a structured strategy and active community participation.